Measurement of Listening and Reading Comprehension Skills in Students of English Pedagogy in a Chilean University - Cisterna-Zenteno, Cecilia (2016)
The article presents the results of an investigation aimed at measuring the skills of reading comprehension and listening comprehension of English pedagogy students in a Chilean university. Three standardized tests from ESOL Cambridge University were applied to students in second, third and fifth years, respectively:  Key English Test (KET), Preliminary English Test (PET) and First Certificate Exam (FCE). The collected data were analyzed by using SPSS program through descriptive statistics. In addition, these results were supplemented with information gathered from three focus groups which aimed at determining the main difficulties arousing during the execution of the tests. The results revealed that students showed problems in their listening comprehension and reading comprehension abilities in KET and FCE tests, where the latter obtained the lowest level of achievement. On the other hand, in the PET exam, approval scores reached the best level. In the focus groups, students expressed that their main difficulties were: adequate understanding of instructions for each task, high level of concentration required for these exams, and little exposure to trials of this type of measuring instruments. The article raises a possible explanation for the low results in two of the tests, using the concept of plateau effect in the process of learning a language. It concludes with a reflection on the English teacher initial training in Chile, the importance of knowing the content and the challenges facing the educational system, as well as the training institutions based on the new pedagogical standards established by the Ministry of Education.